Association of Cerebral Ischemia With Corneal Nerve Loss and Brain Atrophy in MCI and Dementia - Ponirakis, Georgios; Elsotouhy, Ahmed; Al Hamad, Hanadi; Vattoth, Surjith; Petropoulos, Ioannis N.; Khan, Adnan; Gad, Hoda; Al-Khayat, Fatima; Chandran, Mani; Ramadan, Marwan; Elorrabi, Marwa; Gadelseed, Masharig; et al. (Frontiers in Neuroscience, 2021)
Introduction: This study assessed the association of cerebral ischemia with neurodegeneration in mild cognitive impairment (MCI) and dementia. Methods: Subjects with MCI, dementia and controls underwent assessment of cognitive function, severity of brain ischemia, MRI brain volumetry and corneal confocal microscopy. Results: Of 63 subjects with MCI (n=44) and dementia (n=19), 11 had no ischemia, 32 had subcortical ischemia and 20 had both subcortical and cortical ischemia. Brain volume and corneal nerve measures were comparable between subjects with subcortical ischemia and no ischemia. However, subjects with subcortical and cortical ischemia had a lower hippocampal volume (P<0.01), corneal nerve fiber length (P<0.05) and larger ventricular volume (P<0.05) compared to those with subcortical ischemia and lower corneal nerve fiber density (P<0.05) compared to those without ischemia. Discussion: Cerebral ischemia was associated with cognitive impairment, brain atrophy and corneal nerve loss in MCI and dementia.